A Treaty for Local Governments - Potaka, Tama (Victoria University of Wellington Law Review, 1999)
There is a vast literature on the Treaty of Waitangi. However, a large number of constitutional issues such as who owes Treaty obligations and the nature and extent of these obligations are not clear. Instead, such issues are often obscured by the media sensationalising Treaty settlement processes, Maori fisheries, and Pakeha political assumptions about what Maori want. Amidst talk of fish, cash settlements and development, little Treaty jurisprudential thinking addresses the complex legal, cultural and economic issues surrounding local government and Máori. It is the purpose of this article to expand Treaty jurisprudential thinking in the area of local government, and to advocate a direction for local government Treaty obligations.